BROWN SENDROMU - DİKİCİ, Kemal (Cerrahpaşa Medical Journal, 2019)
Background.. The purpose of this study is to evaluate the follow-up of Brown’s syndrome Design.- Thirty four patients ranging in age between 10 months and 24 years were included in this study. Complete ophthalmological examination were performed. Deviation angle was measured by prism bar. Results.- 4 patients had bilateral, 19 had right Brown’s and 11 had left Brown’s syndrome.7 of 37 patients (20.58%) had ambliopia. 6 patients underwent superior oblique tenetomy, 2 inferior oblique total myectomy and one patient silicone band expander. Conclusion.- Follow-up is important for Brown’s syndrome. Operation is indicated in selective cases for correction.